(untitled) (International conference on multidisciplinary science, 2025)
Tomatoes are the most consumed type of vegetables. A number of insects cause serious damage to tomatoes. Among them, the tomato moth is considered a serious p est of leaves and fruits. This article describes the effectiveness of drugs used against tomato moth.